Efficient manufacturing of automobile spark plugs : A six-sigma materials re-engineering case - Berrúm, Rafael; Castano, Victor (International Journal of Engineering and Technology, 2016)
The processing defects of an World-class spark plugs-producing company are described, in terms of the Technology Management challenges involved. The full analysis of this complex situation, which involved 3 plants within the same factory, in terms of a Six Sigma approach, is explained, as well as the simple rengineering proposal, which led to an improvement from 2.47 Sigma to 5.32 Sigma in some specific cases, along with significant savings due to less product rejection and waste material.